Optimization of the Resmob Unit of Grobogan Police Station’s Crime Unit in Revealing the Crime of Vehicle Theft - Fermana, Muhammad Ego (Advances in Police Science Research Journal, 2024)
Vehicle theft in Grobogan is a long-standing problem. Due to many houses of the citizens are in remoted areas and the lack of CCTV around have made the theft even more daring to carry out their actions. In the year of 2022, the crime clearance of vehicle theft had come down from the previous year. Due to that research must be conducted to find the cause of the decline and determine the things that must be improved upon. The purpose of the research the writer conducted was to describe the problem of vehicle theft that occurred in the jurisdiction of the Grobogan Police Station and what are the efforts of the Resmob Unit and what should be improved upon. The type of research that the writer use is a qualitative research with descriptive analysis methods where this method finds the facts of problems in the field and then analyzed using related theories. The theory the writer use are POAC Management theory and the Management Operation 5M theory. The concepts used in this research are the vehicle theft concept and and the investigation concept In order to find the problems that causes the decline in crime solving rate in the Resmob Unit, A research is conducted in the region of Grobogan’s police station’s jurisdiction. After finishing the research, the writer has made the solutions necessary to solve the problem that occurs in the Resmob Unit. It is done by giving the knowledges in the management of the Unit. The knowledge will then be turned into skills by having trainings right in the work of The Resmob Unit. After it has been conducted, the members of the Unit that exels must be given reward by the leaders in the Grobogan police station. With this solution, it is hoped that will increase the successful rate of vehicle theft cases solved in Grobogan.